2000
DOI: 10.1038/sj.pcan.4500399
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of curcumin in human prostate cancer—I. curcumin induces apoptosis in both androgen-dependent and androgen-independent prostate cancer cells

Abstract: In an effort to ®nd an alternative nontoxic means of inducing the apoptosis potential in both androgen-dependent and hormone refractory prostate cancer cells, attention was focused on curcumin (turmeric), traditionally used in medicine and cuisine in India and other south-east Asian countries. The results indicate that curcumin is a novel and potent inducer of apoptosis in both androgen-dependent and androgen-independent prostate cancer cells. This was accomplished by down-regulating apoptosis suppressor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 21 publications
3
91
0
Order By: Relevance
“…2,3 Recently, curcumin has become a focus of interest with regard to its possible antitumor effects in prostate cancer. [12][13][14][15][16][17][18] This study shows for the first time, to our knowledge, that curcumin exerts an inhibitory effect on the invasiveness of DU-145 prostate cancer cells, and confirms this via both in vitro and in vivo testing.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…2,3 Recently, curcumin has become a focus of interest with regard to its possible antitumor effects in prostate cancer. [12][13][14][15][16][17][18] This study shows for the first time, to our knowledge, that curcumin exerts an inhibitory effect on the invasiveness of DU-145 prostate cancer cells, and confirms this via both in vitro and in vivo testing.…”
Section: Discussionsupporting
confidence: 78%
“…This observation was previously reported in both androgen-dependent and androgen-independent prostate cancer cell lines. 12,14,16 Cytochrome c has been determined to function via the formation of a multicomplex, and subsequently initiates a cascade of caspase activations during chemically induced apoptosis. We identified the activation of cytochrome c, caspase-9, and poly ADP-ribose polymerase (PARP) after curcumin treatment via Western blotting (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although a role for bTREK-1 channels in the therapeutic actions of curcumin hasn't been demonstrated, several interesting possibilities exist. Most notably, curcumin shows promise in the treatment of human prostate cancer, where it induces apoptosis of prostate cancer cells [25][26][27]. Remarkably, it has been shown that TREK-1 K + channels are expressed in human prostate cancers, but not in normal prostate cells.…”
Section: Discussionmentioning
confidence: 99%
“…1), a bis-α,β-unsaturated β-diketone found in the rhizomes of the herbaceous plant turmeric, has been extensively studied due to its biological effects, especially its anticancer properties. Curcumin has significant anti-proliferative effects towards various human cancer cell lines derived from prostate, large intestine, bone, and white blood cells [1][2][3][4]. In addition, curcumin has been shown to have a degree of tumor specificity, targeting malignant cells in preference to non-malignant cells [5] and it is effective at low micromolar concentrations [6].…”
Section: Introductionmentioning
confidence: 99%